Operational risk : - Lewis, Nigel Da Costa (Wiley, 2004)
A valuable reference for understanding operational risk Operational Risk with Excel and VBA is a practical guide that only discusses statistical methods that have been shown to work in an operational risk management context. It brings together a wide variety of statistical methods and models that have proven their worth, and contains a concise treatment of the topic. This book provides readers with clear explanations, relevant information, and comprehensive examples of statistical methods for operational risk management in the real world. Nigel Da Costa Lewis, PhD (Stamford, CT), is the Senior Quantitative Risk Manager, responsible for statistical methods, at AIG Trading Group Inc., which is part of the American International Group Inc., the world's leading U.S.-based international insurance and financial services firm